2014
DOI: 10.1152/japplphysiol.01133.2013
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body denervation prevents fasting hyperglycemia during chronic intermittent hypoxia

Abstract: Obstructive sleep apnea causes chronic intermittent hypoxia (IH) and is associated with impaired glucose metabolism, but mechanisms are unknown. Carotid bodies orchestrate physiological responses to hypoxemia by activating the sympathetic nervous system. Therefore, we hypothesized that carotid body denervation would abolish glucose intolerance and insulin resistance induced by chronic IH. Male C57BL/6J mice underwent carotid sinus nerve dissection (CSND) or sham surgery and then were exposed to IH or intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 81 publications
5
55
3
Order By: Relevance
“…terial chemoreceptors. In humans and animals, various forms of hypoxia-induced glucose intolerance may be significantly attenuated by sympathetic blockade or by chemoreceptor denervation (Peltonen et al, 2012;Jun et al, 2014;Shin et al, 2014). Chronic activation of the sympathetic nervous system may be a pathway toward the development of metabolic syndrome (Brotman et al, 2002).…”
Section: Figmentioning
confidence: 99%
“…terial chemoreceptors. In humans and animals, various forms of hypoxia-induced glucose intolerance may be significantly attenuated by sympathetic blockade or by chemoreceptor denervation (Peltonen et al, 2012;Jun et al, 2014;Shin et al, 2014). Chronic activation of the sympathetic nervous system may be a pathway toward the development of metabolic syndrome (Brotman et al, 2002).…”
Section: Figmentioning
confidence: 99%
“…By contrast, Polak et al [12] isolated hepatocytes from mice after 14 days of IH and revealed increased total glucose output as compared to cells from control mice, which was attributed to increased gluconeogenesis. Shin et al [13] also reported increased baseline hepatic glucose output and liver PEPCK transcription in lean mice after 6-week IH exposure. Potentially, the lower PEPCK transcription that we observed from hepatocytes in response to IH does not resemble outcomes from these in vivo experiments because of other systemic effects of IH on catecholamines and hormones, or because of differences in experimental technique.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 92%
“…First, this was by design an in vitro study of the isolated metabolic responses of liver cells to IH. In vivo, systemic effects of IH may modify direct hepatic metabolic responses to IH, including autonomic signaling [13], and changes to substrate delivery [32]. Second, as with any in vitro study, there are limitations to the model of IH.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to only enrol men to minimise potential confounding effects of sex differences in anthropometric and polysomnographic characteristics in OSA [9], and we were able to demonstrate an independent association of insulin resistance with OSA severity without need for a control group. While the pathophysiological nature of this relationship remains uncertain, there is evidence that carotid body-mediated sympathetic activation in the setting of chronic intermittent hypoxia may contribute to metabolic abnormalities [10].…”
Section: −2mentioning
confidence: 99%